PENGARUH STRATEGI PEMBELAJARAN EKSPOSITORI OLEH GURU PAK TERHADAP MOTIVASI BELAJAR SISWA KELAS XII SMA SWASTA HKBP 1 TARUTUNG KABUPATEN TAPANULI UTARA T.P. 2019/2020 - Sihombing, Pestaria (IAKN Tarutung, 2020)
This study aims to determine the level of propensity of Expository Learning Strategies by PAK Teachers and the level of student learning motivation tendencies in HKBP 1 Tarutung Private High School 2019/2020 academic year, as well as to determine the positive and significant influence between Expository Learning Strategies by PAK Teachers on learning motivation XII grade students of HKBP 1 Tarutung North Tapanuli Utara District High School 2019/2020 academic year. The hypothesis of this study is: there is a positive and significant influence of expository learning by PAK teachers on the learning motivation of class XII students of HKBP 1 Tarutung North Tapanuli North High School in 2019/2020. This type of research is quantitative descriptive inferential statistical research. The population in this study were all students of class XII HKBP 1 Tarutung Private High School who were Protestant Christians totaling 164 people and the sample was taken 50% of 164 people totaling 82 people. The research instrument was a closed questionnaire. The result of a simple linear equation is Y = 62,59 + 0,424x. T test results show that the t-test value is 3,075 and t-table = 1,667, so the t-count value ˃ ttable (3,075 1,667) can be obtained. Furthermore, the analysis of the data for the hypothesis test with the f test obtained the value of fcount ˃ ftabel (9,46 3,11) so that it can be concluded that the hypothesis is accepted and based on the results of the coefficient of determination obtained the magnitude of the influence of expository learning by PAK teachers on the learning motivation of class XII high school students Private HKBP 1 Tarutung Utara Tapanuli Regency 2019/2020 Academic Year is 10,56% and another 89,44% is obtained from other inherent factors which are not examined in this study.Keywords: Expository Learning Strategies By PAK Teachers, Student Learning Motivation